Therapeutic mechanism and clinical application of Chinese herbal medicine against diabetic kidney disease - Chen, Dan-Qian; Wu, Jun; Li, Ping (Frontiers in Pharmacology, 2022)
Diabetic kidney disease (DKD) is the major complications of type 1 and 2 diabetes, and is the predominant cause of chronic kidney disease and end-stage renal disease (ESRD). The treatment of DKD normally consists of controlling blood glucose and improving kidney function. The blockade of renin angiotensin aldosterone system and the inhibition of sodium glucose cotransporter 2 (SGLT2) have become the first-line therapy of DKD, but such treatments have been difficult to effectively block continuous kidney function decline, eventually resulting in kidney failure and cardiovascular comorbidities. The complex mechanism of DKD highlights the importance of multiple therapeutic targets in DKD treatment. Chinese herbal medicine (active compound, extract and formula) synergistically improves metabolism regulation, the inhibition of oxidative stress and inflammation, the modulation of mitochondrial dysfunction, and the regulation of gut microbiota and related metabolism via modulating GLP-receptor, SGLT2, Sirt1/AMPK, AGE/RAGE, NF-κB, Nrf2, NLRP3, PGC-1α, and PINK1/Parkin pathways. Clinical trials prove the reliable evidences for Chinese herbal medicine against DKD, but more efforts are still needed to ensure the efficacy and safety of Chinese herbal medicine. Additionally, the ideal combined therapy of Chinese herbal medicine and conventional medicine normally yields more favorable benefits on DKD treatment, laying the foundation for novel strategies to treat DKD.